Do clients business scandals affect the reputation of Audit firms? - Quick, Reiner (My University, 2019)
The auditor is required to obtain reasonable assurance about whether the financial statements as a whole are free from material misstatement, whether due to fraud or error. Reputation is essential in the audit industry. Business scandals can threaten the reputation of the involved auditor
Keywords: Auditoría; Fraude; reputación firmas de autorías; escándalos contables